2020
DOI: 10.1155/2020/4587024
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Applications of Cannabinoids in Cardiomyopathy and Heart Failure

Abstract: A large number of cannabinoids have been discovered that could play a role in mitigating cardiac affections. However, none of them has been as widely studied as cannabidiol (CBD), most likely because, individually, the others offer only partial effects or can activate potential harmful pathways. In this regard, CBD has proven to be of great value as a cardioprotective agent since it is a potent antioxidant and anti-inflammatory molecule. Thus, we conducted a review to condensate the currently available knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 99 publications
2
14
0
Order By: Relevance
“…27 CBD can limit cardiac injury by improving the antioxidant capacity of cells and alleviating apoptosis caused by the mitochondrial death pathway. 33 CBD restores ATP levels and mitochondrial function, reduces oxidative damage, and prevents cardiomyocytes from entering the apoptosis phase in rats poisoned with aluminum phosphide (AlP). 61 This study also found that CBD treatment can protect cardiomyocytes from PFOS-induced oxidative stress, thereby alleviating PFOSinduced mitochondrial dynamic imbalance and energy metabolism disorder, suggesting that CBD can ameliorate PFOS-induced heart injury by controlling myocardial apoptosis mediated by the mitochondrial death pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 CBD can limit cardiac injury by improving the antioxidant capacity of cells and alleviating apoptosis caused by the mitochondrial death pathway. 33 CBD restores ATP levels and mitochondrial function, reduces oxidative damage, and prevents cardiomyocytes from entering the apoptosis phase in rats poisoned with aluminum phosphide (AlP). 61 This study also found that CBD treatment can protect cardiomyocytes from PFOS-induced oxidative stress, thereby alleviating PFOSinduced mitochondrial dynamic imbalance and energy metabolism disorder, suggesting that CBD can ameliorate PFOS-induced heart injury by controlling myocardial apoptosis mediated by the mitochondrial death pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, energy metabolism disorders caused by mitochondrial dysfunction further aggravate PFOS-induced apoptosis . CBD can limit cardiac injury by improving the antioxidant capacity of cells and alleviating apoptosis caused by the mitochondrial death pathway . CBD restores ATP levels and mitochondrial function, reduces oxidative damage, and prevents cardiomyocytes from entering the apoptosis phase in rats poisoned with aluminum phosphide (AlP) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, brain hypoxemia, often silent, occurs also with COVID-19, potentially inducing long lasting sequelae even after remission. Furthermore, CBD mitigates in vivo widely differing forms of cardiomyopathies as has been shown in various animal models including ischemia/reperfusion arrhythmias, myocardial infarction, autoimmune myocarditis or diabetic cardiomyopathy (reviewed recently by [34,35]). This includes also a mouse model of doxorubicin-induced cardiotoxicity [36].…”
Section: Cbd Reduces Neuroinflammationmentioning
confidence: 95%
“…Under pathological conditions of CH, the activities of ATP synthase and mitochondrial oxidative phosphorylation complex are attenuated, which results in reduced production of ATP [12,13]. Moreover, attenuated mitochondrial dynamics, reduced mitochondrial volume, and abnormal mitochondrial morphology were detected in cardiomyocytes in CH [14,15]. Mitochondrial dysfunction was shown to increase the production of reactive oxygen species (ROS) via impaired electron transport chains, which can lead to increased oxidative stress and decreased energy production in cardiomyocytes [9,16,17].…”
Section: Introductionmentioning
confidence: 99%